2014
DOI: 10.1016/j.tsf.2014.06.060
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of nanoindentation pile-up in bulk materials and thin films

Abstract: This work is licensed under a Creative Commons Attribution-NonCommercial 3.0 Unported License Newcastle University ePrints -eprint.ncl.ac.uk Moharrami N, Bull SJ. A Comparison of Nanoindentation Pile-up in Bulk Materials and Thin Films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 35 publications
5
25
0
Order By: Relevance
“…It is seen that both results are well correlated since it agrees with finite element solutions. We can point out that the values determined for the elastic properties correspond to typical values reported in the literature for Si 3 N 4 [7,10,13] and Aluminum [14][15].…”
Section: Resultssupporting
confidence: 82%
“…It is seen that both results are well correlated since it agrees with finite element solutions. We can point out that the values determined for the elastic properties correspond to typical values reported in the literature for Si 3 N 4 [7,10,13] and Aluminum [14][15].…”
Section: Resultssupporting
confidence: 82%
“…These images can be used to map the surface of the materials before indentation to understand where the indentation takes place in addition to understanding, for example, the effects of surface roughness on the data obtained. Mapping the surface of the samples by AFM after indentation tests can be used to measure the true contact area in case of appearance of pile-up or sink-in [23]. Prior to the nanoindentation tests, the Oliver and Pharr method [24] was used to calibrate both the instrument stiffness and the tip-end shape.…”
Section: Nanoindentation Testingmentioning
confidence: 99%
“…Here we exclude the AFM photodetector nonlinearity and scanner creep by using a closed-loop scanner and calibrating the photodetector. Besides, several studies have confirmed that there are some errors in the measured mechanical properties due to the influence of the substrate on the results [50][51][52]. However, the substrate effect is neglected in this work.…”
Section: Resultsmentioning
confidence: 62%